2017
DOI: 10.4314/jfas.v9i3.20
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of arthropods on <i>Sesbania acuelata</i> in the Algerian Sahara and quantification of phenolic compounds by HPLC

Abstract: The present study was carried and knowledge of arthropods which are successfully infecting a plant newly introduced in Algeria in this case Sesbania acuelata. are collected using three methods: pitful The survey resulted in the retri families and 13 orders. The results thus obtained showed a predominance of the order Hymenoptera followed by Diptera and Orthoptera. The Order of the acari is the least represented. For a better qualitative and quantitative analysis of the species identified, numerous ecological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our previous study reported that the leaves of S . bispinosa are a potential source of natural antioxidants given their richness in polyphenols (Larkem et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study reported that the leaves of S . bispinosa are a potential source of natural antioxidants given their richness in polyphenols (Larkem et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds exhibit several pharmacological properties, among which we will cite the antibacterial, anti-inflammatory, vasodilator anticarcinogenic, antithrombotic, anti-atherogenic, antipyretic, and analgesic (Gómez-Caravaca et al, 2006;Muanda, 2011). Our previous study reported that the leaves of S.bispinosa are a potential source of natural antioxidants given their richness in polyphenols (Larkem et al, 2017).…”
mentioning
confidence: 99%